1998
DOI: 10.1007/s002239900407
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-1 mRNA Expression and Proliferation of Human Osteoblastic Cells in Nonosteoporotic and Osteoporotic Women under Influence of TGFβ-1 and IGF-I

Abstract: Currently, primary osteoporosis is the most frequent metabolic disease in women after menopause [1]. The resulting loss of bone mass is accompanied by an increased risk of skeletal fragility. One reason for the development of osteoporosis might be an impaired function of mature osteoblasts. To evaluate the involvement of specific growth factors in bone remodeling, cell cultures of osteoblastic cells derived from nonosteoporotic and osteoporotic postmenopausal women were established. The influences of TGF beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…19,20 Varying results have been obtained by different authors when comparing healthy osteoblasts with cells from osteoporotic patients. Even if the phenotype characterisation did not show variations between normal and osteopenic-bone-derived cells, differences in the rate of proliferation 21,22 or in the response to cytokines, hormones or mechanical stimuli 18,23,24 have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Varying results have been obtained by different authors when comparing healthy osteoblasts with cells from osteoporotic patients. Even if the phenotype characterisation did not show variations between normal and osteopenic-bone-derived cells, differences in the rate of proliferation 21,22 or in the response to cytokines, hormones or mechanical stimuli 18,23,24 have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding osteoporosis, which is a health problem of clinical relevance, there are some in vitro studies in which the differences in activation and proliferation rate of cell cultures derived from osteoporotic patients were studied in comparison with normal bone-derived cells. [26][27][28][29] Even if awareness that bone rarefaction may create a gap between bone, and material implantation has already been achieved in in vivo studies, [30][31][32][33] our group was the first to focus the attention on the possibility of using osteopenic bonederived cells also for the evaluation of orthopedic biomaterials, starting from the assumption that devices are often implanted in patients with bone rarefaction due to primary or secondary osteoporosis. It is our opinion that the in vitro evaluation of this clinical situation could improve data on biocompatibility and osteointegration of biomaterials in the initial phases of a research, thus reducing the number of animals required for subsequent in vivo investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of culturing primary osteoblasts from the human skeleton has made it possible to conduct a great amount of research on osteoblasts cultured from osteoporotic patients and elucidate the different dysfunction patterns and responsiveness of cells to therapies (Katzburg et al, 1999;Sasse et al, 1998). Some of these studies have reported that no or little difference exists between healthy and osteoporotic bone-derived osteoblasts in terms of proliferation, synthetic activity and morphology (Lomri and Marie, 1990;Walsh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%